SURVEI MINAT DAN MOTIVASI SISWA PUTRI TERHADAP MATA PELAJARAN PENJASORKES DI SMK SE-KOTA SALATIGA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine the interest and motivation of students in following subjects daughter Penjasorkes at SMK Salatiga in 2013.The population in this study were all students at SMK daughter Salatiga. Sample collection technique using proportional random sampling technique, in order to obtain the daughter of 356 students from 10 vocational - Salatiga. This research method is a survey method using questionnaire data collection techniques. Data analysis technique used is descriptive percentage .The results showed that the students' interest and motivation of the subjects daughter SMK Penjasorkes in Salatiga in 2013 was good. It can be seen from the students' interest towards subjects Penjasorkes daughter who mostly belong to both categories of positions that 67.42 % of students. The results supported the interests of students from several aspects, among others, aspects of feelings, concerns, wishes, and the environment that the average well categorized. So that the interest of the students found the results quite good daughter to Penjasorkes subjects. Results of women's studies student motivation in following the lesson Penjasorkes mostly go in either category position is 57.02 % of the students there. These results are supported from several aspects: physiological needs, the need for security, actualization needs, social needs, and the need for individual awards aspects of the results obtained in both categories except aspects of physiological needs are classified in the excellent category .